Technostress Construct Validity Test with Confirmatory Factor Analysis (CFA) Method - Subchi, Imam; Muhammadiyah, Hilmi; Dewi, Putri Aisyiyah Rachma; Anwar, Moh. Khoerul; Naim, Juanda; Syukrilla, Wara Alfa (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2024)
This study aims to test the construct validity of the technostress instrument using an instrument developed by Ragu-Nathan et al. (2008) contained 20 modified items using the Indonesian language. The research data was obtained from middle adult teaching staff, namely teachers and lecturers aged 35-60 who taught online learning during Covid-19. 212 respondents participated in this study. The test used confirmatory factor analysis (CFA) with first-order per-dimensional, first-order unidimensional, and second-order models. The analysis was done in MPLUS. Based on CFA first-order unidimensional results, the model fits the data with one item discarded (Item 17). The CFA second-order model is also fit according to the goodness criteria with all items being valid except item 6. According to CFA first-order per-dimensional testing, results show that items for three dimensions (techno-overload, techno-complexity, and techno-insecurity) are valid, while the other two dimensions (techno-uncertainty and techno-invasion) are not fit because the number of items is too small. The instrument can be used to measure technostress and is considered to be unidimensional measuring technostress.